Macroparasites of silversides (Atherinopsidae: Odontesthes) in Argentina - Flores, Verónica Roxana (2016)
This study presents new geographical distribution records for the macroparasites of the marine Odontesthes nigricans (Richardson, 1848) (89 wild specimens), and for the freshwater silversides Odontesthes bonariensis (Valenciennes, 1835) (43 wild and 108 cultured specimens), and Odontesthes hatcheri (Eigenmann, 1909) (183 wild specimens) from Argentina. These data represent records of 12 parasite taxa for O. nigricans, 8 for O. bonariensis, and 19 for O. hatcheri, which include digeneans, monogeneans, cestodes, nematodes, acantocephalans, mollusks, copepods, and branchiurans. For cultured O. bonariensis, the records of the present study correspond to the first reports of parasites in the literature. This work provides also data on site of infection, parasite load, and development stages for the parasite species.